PENINGKATAN KOMPETENSI PEDAGOGIK GURU KELAS VI SDN 97/IX TANJUNG KATUNG MELALUI SUPERVISI AKADEMIK - Sri Maryatun (Indonesian Publication Center, 2020)
The background of this research is the low pedagogical competence of teachers in SDN 97 / IX Tanjung Katung, Muaro Jambi Regency. The purpose of this study was to improve the pedagogical competence of grade VI teachers at SDN 97 / IX Tanjung Katung, Muaro Jambi Regency through academic supervision. This type of research used in this research is school action research. The activities in this study consist of the stages of planning the action, implementing the action, observing, and reflecting. Data collection techniques using class observation techniques. The observation instrument used was a teacher ability assessment tool (APKG) in the form of: 1) an instrument for assessing the ability of teachers in developing a syllabus, 2) an instrument for assessing the ability of teachers in developing lesson plans, 3) an instrument for assessing the ability of teachers in implementing learning. The data analysis used was a comparative descriptive analysis technique. The quantitative data obtained were described in the form of words or explanations. After that, data comparisons were carried out to ensure that there was an increase in the ability of teachers to prepare lesson plans and increase the ability of teachers in implementation. The results showed the findings that academic supervision could: a) improve the ability of grade VI teachers in developing syllabus in Tanjung Katung, Muaro Jambi Regency by 41%. b) increasing the ability of class VI teachers in compiling lesson plans in Tanjung Katung, Muaro Jambi Regency by 39%. c) increasing the ability of grade VI teachers in implementing learning in Tanjung Katung, Muaro Jambi Regency by 34%.